An explicit and implicit hybrid method for structural topology optimization. Issue 1 (March 2021) - Zhang, Junfeng; Liu, Enhai; Liao, Jingyu
Abstract: In order to improve the manufacturability of topology optimization results, this paper proposes a hybrid method based on explicit description of Moving Morphable Components (MMC) and implicit description of Solid Isotropic Material with Penalization (SIMP). The method uses the global convergence characteristics of SIMP to quickly obtain the main force transfer path of structure, and threshold processing is used to eliminate the problem of gray-scale elements generated by SIMP. Furthermore, a morphological idea is proposed to simplify the structure. Then, components are used to fit the structure and extract its geometric parameters, and transition to the MMC is further optimized. Finally, this paper studies several typical examples, and compares them with the single MMC method from three aspects of design domain components layout, structural compliance values, and structural uniformity. The results show that the structure obtained by hybrid method has smaller structural compliance value and significant increase in the uniformity of the structure size.